Magnetic resonance non-echo planar diffusion-weighted imaging accuracy in detecting cholesteatoma in comparison with clinical and surgical findings. Issue 3 (18th March 2022) - Al Zuhir, N; Zammit-Maempel, I; Yates, P; Dixon, J
Abstract: Objective: Magnetic resonance imaging utilising non-echo planar diffusion-weighted imaging is known to have high sensitivity and specificity in detecting cholesteatoma. Method: Data was retrospectively collected from patients who had undergone non-echo planar diffusion-weighted imaging from 1 January 2010 to 31 December 2016. The ratio of average pixel grey-scale values between the middle-ear lesion, pons and temporal lobe was used to quantify the degree of restricted diffusion and assess the statistical significance to detect cholesteatoma. Results: A total of 107 patients had non-echo planar diffusion-weighted imaging during the study period. Non-echo planar diffusion-weighted imaging shows good specificity and sensitivity with an excellent positive predictive value and accuracy. Analysis of the grey-scale pixel ratio for cholesteatoma detection showed statistically significant results. Conclusion: Non-echo planar diffusion-weighted magnetic resonance imaging is accurate for cholesteatoma assessment. When the middle-ear lesion non-echo planar diffusion-weighted imaging intensity is higher than the ipsilateral temporal lobe, it is highly suggestive of a cholesteatoma formation.